Preparation and in vitro cytocompatibility of chitosan–siloxane hybrid hydrogels. Issue 1 (3rd April 2014) - Shirosaki, Yuki; Hirai, Masashi; Hayakawa, Satoshi; Fujii, Eiji; Lopes, Maria A.; Santos, José D.; Osaka, Akiyoshi
Abstract Injectable systems can be used in minimally invasive surgical applications. Although chitosan–glycerophosphate hydrogel systems are biodegradable and biocompatible, the long periods of time required for their effective gelation have severely limited their clinical application. The challenges currently facing researchers in this field are therefore focused on shortening the gelation time and biocompatibility of these materials to develop hydrogels suitable for clinical application. Chitosan and γ‐glycidoxypropyltrimethoxysilane (GPTMS) hybrids have recently demonstrated good cytocompatibility with respect to human osteoblastic cells (MG63) and human bone marrow cells. Although these precursor sols could form gels under physiological conditions, they required neutralization with a sodium hydroxide solution. In this study, the chitosan–GPTMS hybrid systems were neutralized with glycerophosphate to prepare injectable hydrogels. The results revealed that the gelation time of the hydrogels could be controlled by the amount of GPTMS in the precursor sols. The in vitro cytocompatibility of the hydrogels were evaluated in terms of the proliferation of MG63 cells cultured either directly onto the hydrogels or indirectly onto the cell culture plate under a hydrogel insert. In the former case, the cells showed good attachment and proliferated for up to 7 days. Similar results were observed in the in direct culture. These results suggest that this new chitosan–GPTMS hydrogel could potentially be used as an injectable biomaterial in clinical applications. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 289–299, 2015.